2020
DOI: 10.1111/jcmm.15997
|View full text |Cite
|
Sign up to set email alerts
|

G protein‐coupled oestrogen receptor promotes cell growth of non‐small cell lung cancer cells via YAP1/QKI/circNOTCH1/m6A methylated NOTCH1 signalling

Abstract: Lung cancer is the most prominent cause of global cancer-related death. The five-year mortality is approximately 80% due to unsatisfied early diagnosis and curative therapeutic strategy. 1,2 Non-small-cell lung cancer (NSCLC) accounts for 85% of the total lung cancers and is pathologically subtyped into adenocarcinoma, squamous cell carcinoma (SCC) and large cell carcinoma (LCC). 3 Owing to the improved understanding of NSCLC tumorigenesis and progression, new biomarker-targeted therapies have advanced the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 56 publications
(103 reference statements)
0
53
0
Order By: Relevance
“…Previous studies have linked m 6 A modifications to the development of lung cancer [ 41 ]. Several reports showed that m 6 A writers act as oncogenic-proteins to elevate global m 6 A levels [ 42 , 43 ], while m 6 A erasers decrease global m 6 A levels and act as tumor suppressors [ 44 ]. Compared to the writers and erasers, m 6 A readers are terminal effectors of the m 6 A modifications.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have linked m 6 A modifications to the development of lung cancer [ 41 ]. Several reports showed that m 6 A writers act as oncogenic-proteins to elevate global m 6 A levels [ 42 , 43 ], while m 6 A erasers decrease global m 6 A levels and act as tumor suppressors [ 44 ]. Compared to the writers and erasers, m 6 A readers are terminal effectors of the m 6 A modifications.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, circNOTCH1 served as endogenous competitive circRNA to compete for METTL14 binding. Due to the lack of METTL14, NOTCH1 mRNA appeared to be more stable and tended to be transcribed to high expression of NOTCH1, ultimately leading to initiate NOTCH1-mediated signal pathway 84 .…”
Section: Circrnas-rbps Interaction and Cancersmentioning
confidence: 99%
“…Some of the molecules and cell signaling pathways activated by GPER are adenylyl cyclase, cAMP, calcium mobilization and MAPK. Other cell signaling pathways activated by GPER include EGFR/MARL transactivation, the Hippo/yes-associated protein 1 (YAP)/transcriptional coactivator with PDZ-binding domain (TAZ) pathway and phosphoinositide 3-kinase (PI3K)/Akt pathway ( Figure 3 ) [ 58 , 70 ]. A comprehensive discussion based on the studies conducted on GPER knockout mice confirmed the perception that GPER is in fact an ER with specific physiological functions mediated through nongenomic actions [ 70 ].…”
Section: G-protein-coupled Estrogen Receptors and Non-small Cell Lung Cancersmentioning
confidence: 99%
“…Studies by Avino and associates claimed that GPER-driven activation of insulin-like growth factor-I (IGF-I)/IGF-IR via ERK, p38 and Akt stimulation leads to migration of cancer cells [ 162 ]. A recent investigation by Shen and colleagues revealed an oncogenic activity of GPER on NSCLC cells via regulation of YAP1/QKI/circNOTCH1/m6A methylated NOTCH1 mRNA signaling [ 58 ]. In contrast to these studies, some other investigations claimed that GPER activation inhibited migration of human NSCLC cells via suppressed IKK-β/NF-κB signaling pathways [ 57 ].…”
Section: G-protein-coupled Estrogen Receptors and Non-small Cell Lung Cancersmentioning
confidence: 99%
See 1 more Smart Citation